Produção, expressão e caracterização da metalocarboxipeptidase recombinante - Fernandes, Gabriela Cabral [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
A mineração no genoma de Chitinophaga sp. (8Mb), uma bactéria gram-negativa, isolada de um consórcio bacteriano degradador de biomassa, permitiu acesso ao gene Cht_4039 que possui um motivo de HEXXH característico para as carboxipeptidases (CPs) termoestáveis da família M32. O gene foi expresso em Escherichia coli e a enzima recombinante (ChtCP) foi purificada e caracterizada bioquimicamente em detalhes. Esta carboxipeptidase apresentou atividade máxima a 65°C, conservando 60% da atividade à 80ºC. O pH ótimo foi de 7.5. Esta metaloenzima foi ativada 100% com Mn2+ e 150% com Co2+. A estrutura cristalina da ChtCP foi determinada a uma resolução de 1,2 Å. Quando em contato com íons metálicos teve seu ponto de fusão (Tm) acrescido em até 50% mantendo sua estrutura nativa. Em resumo, este estudo mostra que a ChtCP é um membro termoestável da família M32 CP que apresenta atividade enzimática em um amplo espectro de temperatura (de 20 °C à 99 °C) e ativação na presença de íons metálicos (Co+2, Cr+2, Mg+2, Mn+2 ou Zn+2), características importantes na aplicação industrial.

Mining in the genome of Chitinophaga sp. (8Mb), a gram-negative bacterium, isolated from a bacterial consortium obtained from decomposable material withdrawn from the sugarcane bagasse deposit at an ethanol plant, allowed access to a predicted putative of 500 amino acids encoded by the Cht_4039 gene has a characteristic HEXXH motif for the thermostable M32 carboxypeptidases (CPs) already studied. The gene was expressed in Escherichia coli and the recombinant enzyme (ChtCP) was purified and characterized biochemically in detail. This carboxypeptidase showed maximum activity at 65 °C, preserving 60% of the activity at 80 °C. The optimum pH was 7.5. This metalloenzyme was activated 100% with Mn 2+ and 150% with Co 2+. The crystal structure of ChtCP was determined at a resolution of 1.2 Å. When in contact with metallic ions had its melting point (Tm) increased in up to 50% maintaining its native structure. In summary, this study shows that ChtCP is a thermostable member of the M32 CP family that exhibits enzymatic activity over a wide temperature range (from 20 °C to 99 °C) and activation in the presence of metal ions (Co+2, Cr+2, Mg+2, Mn+2 or Zn+2), important characteristics in the industrial application.
Production, expression and characterization of recombinant metalocarboxypeptidase
Keywords: caracterização cinética e estrutural; Carboxipeptidase; Metalocarboxipeptidasse; Mineração de genoma; Structural and kinetic characterization; Carboxypeptidase; Metalocarboxypeptidase; Genome mining